2011
DOI: 10.1242/dev.058362
|View full text |Cite
|
Sign up to set email alerts
|

LEUNIG and SEUSS co-repressors regulate miR172 expression in Arabidopsis flowers

Abstract: SUMMARYCentral to the ABCE model of flower development is the antagonistic interaction between class A and class C genes. The molecular mechanisms underlying the A-C antagonism are not completely understood. In Arabidopsis thaliana, miR172 is expressed in the inner floral whorls where it downregulates the class A gene APETALA 2 (AP2). However, what controls this predominantly inner whorl-specific expression of miR172 is not known. We show that the LEUNIG (LUG) and SEUSS (SEU) corepressors repress miR172 expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
67
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(70 citation statements)
references
References 39 publications
2
67
0
1
Order By: Relevance
“…Its main function is in transcriptional co-regulation, together with LEUNIG, in a series of events related to the floral organs and with pronounced expression at the beginning of flowering (Franks et al, 2002;Vaniyambadi et al, 2006;Hashimoto et al, 2008;Bao et al, 2010;Grigorova et al, 2011). This agrees with the results shown in Figure 2, as the expression pattern of this gene was reduced by 70% when buds were next to the anthesis and therefore when all gametic structures had been generated.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Its main function is in transcriptional co-regulation, together with LEUNIG, in a series of events related to the floral organs and with pronounced expression at the beginning of flowering (Franks et al, 2002;Vaniyambadi et al, 2006;Hashimoto et al, 2008;Bao et al, 2010;Grigorova et al, 2011). This agrees with the results shown in Figure 2, as the expression pattern of this gene was reduced by 70% when buds were next to the anthesis and therefore when all gametic structures had been generated.…”
Section: Discussionsupporting
confidence: 73%
“…This agrees with the results shown in Figure 2, as the expression pattern of this gene was reduced by 70% when buds were next to the anthesis and therefore when all gametic structures had been generated. In A. thaliana, functional analysis indicated that SEUSS plays other roles in flower development, specifically in the carpel margin meristems, a vital meristematic structure located at the margins of the fused carpels and that gives rise to several structures in the female reproductive system, including the eggs (Franks et al, 2002;Azhakanandam et al, 2008;Grigorova et al, 2011;Kamiuchi et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Azhakanandam et al, 2008;Bao et al, 2010;Nole-Wilson et al, 2010;Lee et al, 2014). Interestingly, although SEU does not appear to possess a recognizable DNA-binding motif, it was shown by chromatin immunoprecipitation (ChIP) to associate with cis-regulatory elements located in the second intron of the floral homeotic gene AGAMOUS (AG; Sridhar et al, 2006) and with cisregulatory elements of miR172 genes (Grigorova et al, 2011). Hence, SEU likely regulates gene expression through interactions with DNA-binding transcription factors.…”
mentioning
confidence: 99%
“…Petal identity is fixed in the second whorl by the combined function of class A, B, and E genes (Bowman et al, 1989;Weigel and Meyerowitz, 1994;Krizek and Fletcher, 2005). Suppression of AGAMOUS activity in the perianth whorls is important for petal growth, and this process is controlled by AP2, AINTEGUMENTA, LEUNIG, SEUSS, RABBIT EARS, ROXY1, and STERILE APETALA (Liu and Meyerowitz, 1995;Byzova et al, 1999;Conner and Liu, 2000;Krizek et al, 2000Krizek et al, , 2006Franks et al, 2002;Sridhar et al, 2004;Xing et al, 2005;Grigorova et al, 2011). Petal primordia arise at four loci in the second whorl, and this positioning is established independently of the process that determines organ identity (Griffith et al, 1999;Brewer et al, 2004;Takeda et al, 2004;Xing et al, 2005;Lampugnani et al, 2013).…”
mentioning
confidence: 99%